Disaster Discourse, Delayed States, and Civic Counter-Narratives: A Critical Sociolinguistic Study of “Citizens Helping Citizens” in Sumatra - Andesta, Heri Wira; Saragih, M Afiv Toni Suhendra; Purnama, Anton (English Teaching and Linguistics Journal (ETLiJ), 2026)
This article examines disaster discourse in Sumatra by analyzing how the state and citizens are represented in public communication during the emergency response phase. Employing a Critical Discourse Analysis approach within sociolinguistics, the study analyzes a corpus of national online news reports and citizens’ social media posts. The analysis focuses on the representation of social actors, lexical strategies, evaluative structures, and temporal constructions that shape meanings of delay, action, and accountability. The findings reveal that state discourse is dominated by institutional and procedural language that tends to obscure agency and normalize delayed responses as technical matters. In contrast, citizen discourse constructs a powerful counter-narrative of citizens helping citizens, foregrounding horizontal solidarity while implicitly challenging state legitimacy. This discursive tension demonstrates that disasters are socially and linguistically produced rather than neutrally reported. The study contributes to sociolinguistic research on disaster discourse by providing empirical evidence from the Global South and highlighting the role of counter-discourse in reshaping power relations, responsibility, and public trust in times of crisis.